Feasibility of once-through cooling for 50MWe solar thermal power plant on / near the lower Orange River. - Kehinde, Abiole Gboyega (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.